Introgression shapes the genomic conflict landscape of Malus, providing evidence for a reticulate backbone in a woody crop lineage - Xiao-Ya Li; Zhao-Qian Niu; Ya-Wen Zheng; Jue-Lin Huang; Dai-Kun Ma; Jia-Xin Huang; Qiang Hao; Ti-Cao Zhang; Si-Yu Xie; Chao Xu; Bin-Bin Liu (Molecular Phylogenetics and Evolution, 2026)

The interplay between extracellular matrix remodeling and cellular lipid metabolic reprogramming in cancer: a review - Minyue Yin; Xue Li; Shutian Zhang; Si-An Xie (Molecular Biology Reports, 2026)

A mechanism-constrained large language model-based intelligent diagnosis framework for bridge defects - Hui Jin; Si-Ming Zhou; Han Chen; Zhi-Yu Xie; Feng Li; Yong Li; Jian-Feng Zhu; Yi-Feng Ling; Zhi-Min Wu; Xiang-Ming Zhou (Engineering Structures, 2026)

Unveiling the cooling mechanism of strontium and copper oxalates as coolants in a 5‑Aminotetrazole Propellant: Modulating pyrolysis and combustion performance - Si-Yuan Zhou; Xuan Li; Qing Chen; Zhong-Wei Hu; Dan Zhang; Zhong-min Xiao; Li-Feng Xie; Mi Li; Andrei Rotaru (Fuel, 2026)

Future decline in the sensitivity of carbon use efficiency to soil formation rates in global karst ecosystems - Hui Chen; Renru Wang; Peirou Yang; Xinyue Li; Si Li; Lian Xiong; Chaochao Du; Xiaodong Yuan; Shiqi Tian; Junhan Li; Jingjing Liao; Sirui Zhang; et al. (CATENA, 2026)

Directivity effect of ground motions of the 2024 Mw7.4 Hualien Earthquake in Taiwan, China - Liang Qian; Jin-Cheng Li; Qiang Ma; Quan-Cai Xie; Xiao-Nan Zhang; Si-Han Yu (Applied Geophysics, 2026)

Silicon carbide (SiC) as antioxidant coating in solid-state lithium target for accelerator-based boron neutron capture therapy (AB-BNCT) - Yixin Si; Jinglun Li; Fanxi Zhang; Yaru Wang; Chen Chen; Shixi Chen; Xuanyu Meng; Yaocheng Hu; Yupeng Xie; Xiaozhi Zhang; Sheng Wang (Annals of Nuclear Energy, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Denosumab safety in men with osteoporosis: a disproportionality analysis of the FAERS database - Hou-hong Li; Li Wan; Si-jie He; Wen-long Xie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Early Miocene Populus L. Fossils Reveal the Northwestward Expansion of the East Asian Summer Monsoon Into Eastern Qaidam - Zhen‐Dong Cao; San‐Ping Xie; Jing‐Nan Huang; Yun‐Zhe Zhang; Zi‐Yi Li; Si‐Hang Zhang; De‐Fei Yan (Journal of Biogeography, 2026)
Aim The evolution of the East Asian Summer Monsoon (EASM) is critical for understanding Asian biodiversity and ecosystem stability. While models and geological records suggest the EASM reached the Qaidam Basin during the Miocene, macrofossil evidence remains scarce. We aimed to test the hypothesis of a northwestward monsoon expansion using newly discovered Populus fossils as bioclimatic indicators. Location Wulan Basin, northeastern Tibetan Plateau, Qinghai Province, China. Taxon Angiosperms (Salicaceae: Populus L.). Methods We conducted morphological analyses on leaf fossils and identified their Nearest Living Relative (NLR). By establishing correlations between the leaf traits of the NLR and modern climatic factors, we reconstructed the paleoclimate of the Wulan Basin. Furthermore, we employed Species Distribution Modelling (MaxEnt) to simulate the potential range of this lineage under Early Miocene conditions to explore monsoon‐driven habitat shifts. Results The late Early Miocene fossils from the Wulan Basin are morphologically most similar to the extant Populus davidiana , a species characteristic of temperate, semi‐humid environments. The presence of this lineage indicates that the Wulan Basin—currently an arid region—experienced significantly higher precipitation and a temperate semi‐humid climate during the Early Miocene. MaxEnt modelling reveals that the suitable bioclimatic envelope for this Populus group extended much further northwest than its modern range, providing a potential biological signal of enhanced moisture transport into the interior of East Asia. Main Conclusions The occurrence of Populus fossils in the Wulan Basin provides a preliminary biological indicator for the northwestward expansion of the EASM into the northeastern Tibetan Plateau during the late Early Miocene, although corroboration from additional proxy records and localities is still needed. This climatic shift, likely driven by the phased uplift of the Tibetan Plateau, transformed the regional hydrological cycle and facilitated the migration of mesic woody taxa into Asia's interior. Our findings highlight the profound impact of tectonic‐monsoon interactions on historical plant distributions.

Environmental VOC exposure and mental health - Jianhui Guo; Feifei Si; Ran Huang; Xinlu Wang; Yuqi Shi; Guiying You; Yaqi Wang; Di Shi; Xinyao Lian; Shuyue Li; Junyu Lu; Shaodong Xie; et al. (Journal of Hazardous Materials, 2026)

Artesunate overcomes oxaliplatin resistance in colorectal cancer by inducing ferroptosis through inhibition of the CDK5/Nrf2/GPX4 pathway - Feng Lv; Xiao-huan Li; Si-qi Li; Hao-wei Deng; Hao-tang Wei; Ke-zhi Li; Ming-zhi Xie; Li-ye Xie; Shu-fang Ning; Bang-li Hu (Apoptosis, 2026)

Terpenes from Platycladus orientalis and the evaluation of their potential anti-inflammatory activity - Yi-Fan Xie; Song-Xue Yang; Xue-Wen Wu; Bo Li; Si-Chen Song; Qiong Wei; Xing-Jie Zhang; Xiao-Li Li; Wei-Lie Xiao (Natural Product Research, 2026)

First report of Neopestalotiopsis iberica causing needle blight on Pinus massoniana - Kai-Yue Lü; Si-Yi Zhang; Yu Wan; Si Li; Jun-Ya Xie; De-Wei Li; Li-Hua Zhu (Crop Protection, 2026)

Elucidating the pyrolytic mechanisms of clean and safe gas generator 5-amino-1H-tetrazole/SiO2: A comprehensive kinetic and theoretical investigation - Si-Yuan Zhou; Xuan Li; Yuan-Hui Liu; Hao-Tian Zhou; Peng-Cheng Xi; Dan Zhang; Mi Li; Li-Feng Xie (Fuel, 2026)

The causal relationship between polycystic ovary syndrome and structural changes in brain: a Mendelian randomization study - Han Yang; Wei Xie; Camilo Alberto Pinzon Galvis; Si Huang; Xu He; Si-yi Yu; Qing You; Fan-rong Liang; Zhi-yong Xiao; Ning Li (Brain Imaging and Behavior, 2026)

From modeling to therapy: the efficient and precise tools for mitochondrial base editing - Si-Si Xie; Xiang Li; Hao Yin (Science China Life Sciences, 2026)

Soil microplastics at different depths before and after mechanical harvesting: case study in Anhui Province, China - Shi-hao Zhao; Di Dai; Yu-xin Tan; Si-yao Li; Bing-yu Chen; Qian Wang; Long Chen; Ji-yue Wang; Shu-guang Zhu; Fa-zhi Xie (Environmental Monitoring and Assessment, 2026)

Nanobubble aeration accelerates manure wastewater sanitisation and enhances nitrogen retention while reduces greenhouse gas emissions - Shance Hou; En Xie; Buchun Si; Yang Xiao; Jingtao Ding; Zhuoyu Yan; Haibin Zhou; Hongsheng Cheng; Yujun Shen; Yunkai Li (Water Research, 2026)

Procyanidin C1 from hawthorn modulates metabolic-inflammatory axis to combat vascular senescence in atherosclerosis - Min Li; Jia-Yao Si; Peng-Fei Xie; Zhen-Jie Feng; Sheng-Jie Li; Feng Zhou; Jian-Mei Li (Food Research International, 2026)

Suffusion in shield tunnel surrounding soils under train vibration using an improved DEM-PNM coupling method - Si-Rui Chen; Dong-Mei Zhang; Xiao-Chuang Xie; Zhao-Geng Chen; Hui-Hao Chen; Hai-Yun Li (Tunnelling and Underground Space Technology, 2026)

Interpenetrated hierarchical polyzwitterionic hydrogels promote decellularized small-diameter vascular grafts regeneration - Qi-Ying Wu; Chun-Yang Chen; Jin-Chang Li; Ze-Guo Chen; Si-Cheng Chen; Chao Xie; Si-Xi Liu; Zi-Han Liu; Zhong-Shi Wu; Yu-Hong Liu (Chemical Engineering Journal, 2026)

Reductive Dechlorination of Trichloroethene by Carboxymethyl Cellulose Stabilized and Sulfidated Nanoscale Zero-Valent Iron: Effect of Humic Acid - Bo Chen; Qi Li; Yuhan Hang; Si Chen; Zihan Xie; Hao Yuan; Yadong Yang; Feng He (Water, Air, & Soil Pollution, 2026)

Plasma MicroRNA and Protein Signature Associated with Obesity in the Chinese Han Population Using MicroRNA Omics and Proteomics Analysis of 1026 Subjects - Yun-Xia Xie; Jian-Ge Qiu; Zhao-Hui Yang; Chen Ding; Le-Ming Shi; Si-Jia Wang; Li Jin; Bing-Hua Jiang (Phenomics, 2026)

Systematic druggable genome-wide Mendelian randomization identifies therapeutic targets for gout - Wei-quan Liao; Hui-ying Chen; Yu-ying Li; Li-juan Xiao; Zai-xing Qiu; Sha-sha Hu; Si-hui He; Lan Luo; Jing-jing Xie; Jian-yong Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Hydrogen diffusion layer within solid-state lithium target for compact accelerator-driven neutron source: Irradiation damage, hydrogen concentration, thermal properties and fabrication - Yupeng Xie; Xiaobo Li; Fanxi Zhang; Yaocheng Hu; Yixin Si; Xuanyu Meng; Qiuyu Sun; Yaru Wang; Chen Chen; Xiaozhi Zhang; Sheng Wang (Annals of Nuclear Energy, 2026)

Highly selective production of 1O2 in Co(OH)2@Co9S8 heterojunction via interfacial electric field modulation for robust water purification - Zhifeng Lin; Longhao Pei; Anqi Wei; Jinhao Xie; Xueding Jiang; Si Liu; Weicheng Xu; Fuhua Li; Xihong Lu (Chemical Engineering Journal, 2025)

Using positive matrix factorization, sensitivity analysis, and machine learning models to identify hydrochemical processes and predict groundwater quality in a typical metropolitan city - Zhan Xie; Jinhang Huang; Denghui Wei; Yangshuang Wang; Si Chen; Shiming Yang; Xingjun Zhang; Chang Yang; Junyi Li; Yunhui Zhang (Stochastic Environmental Research and Risk Assessment, 2025)

The role of canopy family proteins: biological mechanism and disease function - Xue Li; Min-Yue Yin; Shu-Tian Zhang; Si-An Xie (Molecular Biology Reports, 2025)

Tyro3 upregulation is associated with muscle involvement in patients with idiopathic inflammatory myopathies - Huan Liu; Ying Ren; Qianwei Li; Yanjun Si; Yuehong Chen; Min Dong; Geng Yin; Qibing Xie (Immunologic Research, 2025)

CPT1A facilitated ferroptosis by forming feedback loop with Nrf2 via PI3K/AKT pathway in colorectal cancer - Xiao-huan Li; Feng Lv; Si-qi Li; Hao-wei Deng; Li-ping Tang; Ke-zhi Li; Li-ye Xie; Bang-li Hu; Shu-fang Ning (Apoptosis, 2025)

Multiscale responses of gap-graded soil under the combined effect of train vibration and seepage erosion - Dong-Mei Zhang; Hui-Hao Chen; Xiao-Chuang Xie; Si-Rui Chen; Zhao-Geng Chen; Jia-Ping Li (Transportation Geotechnics, 2025)

Concentration-dependent visual SO2 detection from trace to pure in a zirconium MOF - Guang-Rui Si; Xiang-Jing Kong; Lin-Hua Xie; You-Tuo Zhang; Tao He; Jian-Rong Li (Science Bulletin, 2025)

Hydrogen activated the Nrf2/HO pathway to alleviate the cognitive decline in PD Drosophila after long-term sevoflurane exposure - Ming Li; Bo Ma; Si Liang; Xuanyi Pan; Jingyi Xie; Hongjie Wang; Jiguang Guo (Neurotoxicology and Teratology, 2025)

Segmentation and deformation mechanisms of the North Tuole Shan fault in the Qilian Mountains: Insights from channel steepness index (k) and fault activity - Hongqiang Li; Daoyang Yuan; Qi Su; Guojun Si; Hong Xie; Yameng Wen; Ruihuan Su; Yunsheng Yao; Jinchao Yu; Hao Sun (Geomorphology, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Desulfosporosinus sediminicola sp. nov., an acidophilic sulfate-reducing bacterium isolated from acidic sediments of a disused iron mine site - Sheng-Fang Jiang; Chu-Yi Zhang; Xuan-Wen Lao; Wei-Chao Jia; Tao-Tao Yang; Si-Yu Zhang; Ying-Ying Xie; Pei-Zhe Ye; Rui Lan; Zi-Xiang Lai; Qiang Yang; Li-Nan Huang (Antonie van Leeuwenhoek, 2025)

Identification of the exposure pathway to micro-scaled biogenic silica debris via diet and its potential effect in promoting esophageal squamous cell carcinoma - Shenxi Deng; Yi Yang; Erica Celeste Conway; Si Li; Cha Huang; Zigu Chen; Haisheng Wu; Yuan He; Shuzhe Xie; Aifang Ji; Jingyan Zhang; Yansheng Gu; et al. (Journal of Hazardous Materials, 2025)

Engineered exosomal miR140 modulates mitophagy of chondrocytes through targeting CAPN1 to alleviate osteoarthritis - Yuan Liu; Kai Huang; Sheng-Liang Zhou; Shuai Li; Hai-Bo Si; Yi Zeng; Hui-Qi Xie; Bin Shen (Science China Life Sciences, 2025)

Analgesic Effects of Acupressure on Jing-jiaji Acupoints in a Rat Model of Cervical Spondylotic Radiculopathy - Shang-Hong Jiang; Song Yang; Ling Meng; Ling-Yao Xie; Jia-Ni Yang; Si-Qi Li; Ke-Ying Liao; Zhi-Fang Qiu; Yao-Yao Xiao; Man-Di Fu; Zhi-Li Liu; Xue-Yu Jiang (Molecular Neurobiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Novel Chimonanthus teas made from scenting different tea dhools with Chimonanthus praecox flowers - Hao Zuo; Xiongyuan Si; Mangmang Tan; Wenting Li; Jiaomei Xie; Wuxiong Yang; Zhihui Chen; Mingzhi Zhu; Zhi Zhou; Changsong Chen; Zhonghua Liu; Jian Zhao (Food Chemistry, 2025)

Two designed bimetallic sod-ZMOFs with ample active sites for CO2 capture and CO2 cycloaddition - Xueliang Qin; Xueyue Yu; Jincheng Si; Shuyu Xie; Zhaohui Shi; Xu Liu; Chenbo Li; Guanghua Li; Yunling Liu (Chemical Engineering Journal, 2025)

Incidence, risk factors, and prognosis of hospitalized mechanical eye injuries in China: data from China Ocular Trauma Study (COTS) 2021–2023 - Han Han; Yongjie Chen; Gao Si; Guowei Huang; Jiayi Song; Wenfang Zhang; Danyan Liu; Jie Zhong; Xuemin Jin; Dawei Sun; Shenwen Liu; Yanming Huang; et al. (Science Bulletin, 2025)

Experimental study on the reliability of Pt/C-SSWM catalysts applied to hydrogen mitigation: Temperature development mechanism, hydrogen mitigation effect and reaction lower limit - Xuan Li; Si-Yuan Zhou; Tao-Tao Ye; Jing Zhang; Bin Li; Dan Zhang; Yong-Xu Wang; Li-Feng Xie; Xian-Zhao Song (Fuel, 2025)

Atomevo-odor: A database for understanding olfactory receptor-odorant pairs with multi-artificial intelligence methods - Heng-Yun Zhao; Si-Min Xu; Si-Nuo Xie; Wan-Lin Ye; Jian Li; Lang-Hong Wang; Shi-Lin Cao; Jun-Hu Cheng; Xin-An Zeng; Ji Ma (Food Chemistry, 2025)

Seismic experimental research on damaged resilient reinforced concrete columns retrofitted by FRP sheets - Yunjian He; Gaochuang Cai; Cheng Xie; Prafulla Bahadur Malla; Yiyuan Li; Amir Si Larbi (Engineering Structures, 2025)

Manipulating molecular conformation of charge-transfer cocrystal for NIR-II absorption and light/thermal-responsive imaging - Yun Rong; Si-Qi Chen; Yu Dong Zhao; Sheng Zhuo; Yuan-Yuan Li; Jin-Zhuo Liu; Yi-Yi Ju; Yue-Min Xie; Liang-Sheng Liao; Ming-Peng Zhuo; Ke-Qin Zhang (Chemical Engineering Journal, 2025)

Proline betaine facilitates angiogenesis in bronchopulmonary dysplasia - Wangdui Cili; Zhiye Qi; Qinghua Zhong; Yin Li; Xia Huang; Ruoting Yang; Si Tang; Qingyuan Li; Li Yang; Yue Ning; Yunbo Xie; Yanli Feng; et al. (Toxicology and Applied Pharmacology, 2025)

Characterization of two novel angiotensin converting enzyme-inhibitory peptides from yellow tuna peptides: Inhibitory mechanism, transport route and network pharmacology analysis - Jinxin Wang; Si-jie Guo; Xing Xie; Tian-xin Ma; Qin-hui Wen; Yong-lin Gao; Yueming Li; Jian Zhang; Wenjun Li; Lu Zhang (Food Research International, 2025)

Identification of key taste and nutrient components in 12 blueberry varieties using widely targeted metabolomics - Xu Xie; Yuehua Wang; Bosu Wen; Xin Guo; Zhen Cheng; Xu Si; Zhiying Li; Yujie Nie; Jiaqi Yang; Bin Li (Food Bioscience, 2025)

Targeted isolation of lignans and triterpenoids from kadsura coccinea by molecular networking and anti-RA-FLS activity - Shi-qi Liu; Qing-ling Xie; Ya-si Deng; Ling Liang; Han-wen Yuan; Bin Li; Huang-he Yu; Xing Tian; Yi-xing Qiu; Guy Paulin Kemayou Mouthe; Nuzhat Shehla; Ye Zhang; et al. (Phytochemistry, 2025)

Corrigendum to “Rare earth elements in the upstream of Yangtze River Delta: Spatio-temporal distributions, sources and speciations” [Mar. Pollut. Bull. 209 (2024) 117103] - Miao He; Guijian Liu; Yongli Li; Li Zhou; Guanyu Wang; Wen Si; Zongfan Xie (Marine Pollution Bulletin, 2025)

Zero-strain high entropy spinel oxide (FeNiCuCrMn)3O4@rGO as high-performance anode for sodium ion battery - Bin Xiao; Xiaoyang Liu; Zelin Xie; Duyu Zheng; Juxing Zha; Jiqiu Qi; Fuxiang Wei; Qingkun Meng; Xiaolan Xue; Danyang Zhao; Yongzhi Li; Qing Yin; et al. (Chemical Engineering Journal, 2025)

Preventive effect of imperatorin against doxorubicin-induced cardiotoxicity through suppression of NLRP3 inflammasome activation - Hao Zhang; Xiaoyun Ding; Yumei Qiu; Mengdie Xie; Hu Wang; Tingting Li; Huiyun Bao; Si Huang; Yinhua Xiong; Xilan Tang (Journal of Natural Medicines, 2025)

Varied chromosome distribution behaviours during meiosis in triploid Chinese chives contribute to the formation of viable pollen - Peng-Qiang Yao; Li-Hua Xie; Mei-Yu Li; Si-Qian Jiao; Shuai-Zheng Qi; Zhe Wang; Shi-Ping Cheng (Chromosome Research, 2024)

Rare earth elements in the upstream of Yangtze River Delta: Spatio-temporal distributions, sources and speciations - Miao He; Guijian Liu; Yongli Li; Li Zhou; Guanyu Wang; Wen Si; Zongfan Xie (Marine Pollution Bulletin, 2024)

Miocene evolution of vegetation, climate, and elevation in the Wulan Basin of northeast Tibetan Plateau based on a CRACLE analysis of palynological assemblages - Xiao-Mei Li; Jia-Yi Chen; Zhen-Dong Cao; Li-Ming Liu; Si-Hang Zhang; Yun-Zhe Zhang; Li-Jie Wei; San-Ping Xie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Tectonic-climate-wildfire coupling during the Miocene in the northeastern Qinghai-Tibetan Plateau - Li-Ming Liu; Zhen-Dong Cao; Xiao-Mei Li; Si-Hang Zhang; Yun-Zhe Zhang; Jia-Yi Chen; De-Fei Yan; San-Ping Xie (Journal of Asian Earth Sciences, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Multiple anthropogenic environmental stressors structure soil bacterial diversity and community network - Mochen Wu; Siyuan Xie; Jingxi Zang; Yuanze Sun; Shimeng Xu; Si Li; Jie Wang (Soil Biology and Biochemistry, 2024)

Chitinase and proteinase K treatments enhance the DNA yield of microsporidium Ecytonucleospora hepatopenaei spores - Xiao-Meng Guo; Wen Gao; Hai-Liang Wang; Prapatsorn Wongkhaluang; Suparat Taengchaiyaphum; Guo-Si Xie; Chen Li; Ruo-Heng Zhao; Kallaya Sritunyalucksana; Jie Huang (Journal of Invertebrate Pathology, 2024)

Acinetobacter corruptisaponis sp. nov., Isolated from a Spoiled Bath Lotion - Ying-Si Wang; Gang Zhou; Hong-Bing Tao; Lei Gao; Bao-Zhu Fang; Xiu-Jiang Yang; Hong Peng; Xia Wen; Xiao-Mo Huang; Jie Wang; Wen-Jun Li; Qing-Shan Shi; et al. (Current Microbiology, 2024)

Numerical simulation and experimental study of hydrodynamic characteristics of inverted-droplet underwater gas storage devices - Chaoqun Liu; Yingchun Xie; Haoxun Yuan; Jin Qin; Xiangkun Li; Xiancai Si; Yuanlong Tang (Ocean Engineering, 2024)

Crystal phase conversion of amorphous Fe−Mn binary oxides promote the sequestration and redistribution of arsenic, cadmium, and lead in the soil: Comparison with crystalline form - Junhao Zheng; Yan Xie; Yang Ping; Hao Xu; Qi Li; Qi Liao; Qingzhu Li; Zhihui Yang; Weichun Yang; Mengying Si (Journal of Environmental Chemical Engineering, 2024)

Mildly preheating induced conformational changes of soy protein isolates contributed to the binding interaction with blueberry anthocyanins for stabilization - Siyi Tang; Xu Si; Zhihuan Zang; Hailong Gui; Xu Xie; Liang Wang; Ying He; Baoru Yang; Bin Li (Food Hydrocolloids, 2024)

TNF-α and RPLP0 drive the apoptosis of endothelial cells and increase susceptibility to high-altitude pulmonary edema - Yi-Ling Ge; Pei-Jie Li; Ying-Rui Bu; Bin Zhang; Jin Xu; Si-Yuan He; Qing-Lin Cao; Yun-Gang Bai; Jin Ma; Lin Zhang; Jie Zhou; Man-Jiang Xie (Apoptosis, 2024)
High-altitude pulmonary edema (HAPE) is a fatal threat for sojourners who ascend rapidly without sufficient acclimatization. Acclimatized sojourners and adapted natives are both insensitive to HAPE but have different physiological traits and molecular bases. In this study, based on GSE52209, the gene expression profiles of HAPE patients were compared with those of acclimatized sojourners and adapted natives, with the common and divergent differentially expressed genes (DEGs) and their hub genes identified, respectively. Bioinformatic methodologies for functional enrichment analysis, immune infiltration, diagnostic model construction, competing endogenous RNA (ceRNA) analysis and drug prediction were performed to detect potential biological functions and molecular mechanisms. Next, an array of in vivo experiments in a HAPE rat model and in vitro experiments in HUVECs were conducted to verify the results of the bioinformatic analysis. The enriched pathways of DEGs and immune landscapes for HAPE were significantly different between sojourners and natives, and the common DEGs were enriched mainly in the pathways of development and immunity. Nomograms revealed that the upregulation of TNF-α and downregulation of RPLP0 exhibited high diagnostic efficiency for HAPE in both sojourners and natives, which was further validated in the HAPE rat model. The addition of TNF-α and RPLP0 knockdown activated apoptosis signaling in endothelial cells (ECs) and enhanced endothelial permeability. In conclusion, TNF-α and RPLP0 are shared biomarkers and molecular bases for HAPE susceptibility during the acclimatization/adaptation/maladaptation processes in sojourners and natives, inspiring new ideas for predicting and treating HAPE.

A dual-functional NIR fluorescence probe for detecting hypochlorous acid and bisulfite in biosystem - Junyan Ma; Xiangtao Kong; Mingtao Zhao; Zilin Jiao; Hua Xie; Weijie Si; He Li; Zhenxing Zhang (Analytica Chimica Acta, 2024)

Development and application of machine learning models for prediction of soil available cadmium based on soil properties and climate features - Zhihui Yang; Hui Xia; Ziyun Guo; Yanyan Xie; Qi Liao; Weichun Yang; Qingzhu Li; ChunHua Dong; Mengying Si (Environmental Pollution, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Bacteria undergo significant shifts while archaea maintain stability in Pocillopora damicornis under sustained heat stress - Huimin Ju; Jian Zhang; Yiyang Zou; Feiyang Xie; Xiaoyu Tang; Si Zhang; Jie Li (Environmental Research, 2024)

Combined effects of binary mixtures of 17β-estradiol and testosterone in western mosquitofish (Gambusia affinis) after full life-cycle exposure - Chen-Si Wang; Gui-Zhen Fang; Xiao-Pei Li; Guo-Yong Huang; Lingtian Xie; Guang-Guo Ying (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Expression and function identification of senescence-associated genes under continuous drought treatment in grapevine (Vitis vinifera L.) leaves - You-Mei Li; Xuan-Si Tang; Meng-Hao Sun; Hong-Xing Zhang; Zhao-Sen Xie (Physiology and Molecular Biology of Plants, 2024)

SNHG4-mediated PTEN destabilization confers oxaliplatin resistance in colorectal cancer cells by inhibiting ferroptosis - Si-qi Li; Wen-ting Xu; Yi-xin Yin; Hao-tang Wei; Ke-zhi Li; Ming-zhi Xie; Feng Lv; Li-ye Xie; Bang-li Hu (Apoptosis, 2024)

Mechanically treated Mn2O3 triggers peracetic acid activation for superior non-radical oxidation of micropollutants: Identification of reactive complexes - Yudan Dong; Chuan-Shu He; Si Sun; Jiali Liu; Zhi-Hui Xie; Jie-Yuan Li; Peng Zhou; Heng Zhang; Fan Dong; Bo Lai (Water Research, 2024)

Asiaticasics A-O, structurally intriguing coumarins from Toddalia asiatica with potential inflammatory inhibitory activity - Si-Chen Song; Bai-Dong Ren; Xue-Wen Wu; Yi-Fan Xie; Bin Cheng; Qiong Wei; Wen-Hui Pang; Ze-Kai Wu; Xing-Jie Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2024)

Integrated analysis of transcriptome and small RNAome reveals regulatory network of rapid and long-term response to heat stress in Rhododendron moulmainense - Si-Jia Liu; Chang Cai; Hong-Yue Cai; Yu-Qing Bai; Ding-Yue Wang; Hua Zhang; Jin-Gen Peng; Li-Juan Xie (Planta, 2024)
Main conclusion The post-transcriptional gene regulatory pathway and small RNA pathway play important roles in regulating the rapid and long-term response of Rhododendron moulmainense to high-temperature stress. Abstract The Rhododendron plays an important role in maintaining ecological balance. However, it is difficult to domesticate for use in urban ecosystems due to their strict optimum growth temperature condition, and its evolution and adaptation are little known. Here, we combined transcriptome and small RNAome to reveal the rapid response and long-term adaptability regulation strategies in Rhododendron moulmainense under high-temperature stress. The post-transcriptional gene regulatory pathway plays important roles in stress response, in which the protein folding pathway is rapidly induced at 4 h after heat stress, and alternative splicing plays an important role in regulating gene expression at 7 days after heat stress. The chloroplasts oxidative damage is the main factor inhibiting photosynthesis efficiency. Through WGCNA analysis, we identified gene association patterns and potential key regulatory genes responsible for maintaining the ROS steady-state under heat stress. Finally, we found that the sRNA synthesis pathway is induced under heat stress. Combined with small RNAome, we found that more miRNAs are significantly changed under long-term heat stress. Furthermore, MYBs might play a central role in target gene interaction network of differentially expressed miRNAs in R. moulmainense under heat stress. MYBs are closely related to ABA, consistently, ABA synthesis and signaling pathways are significantly inhibited, and the change in stomatal aperture is not obvious under heat stress. Taken together, we gained valuable insights into the transplantation and long-term conservation domestication of Rhododendron , and provide genetic resources for genetic modification and molecular breeding to improve heat resistance in Rhododendron .

Author Correction: Porphyromonas gingivalis promotes the progression of oral squamous cell carcinoma by stimulating the release of neutrophil extracellular traps in the tumor immune microenvironment - Zhi-chen Guo; Si-li Jing; Xin-yu Jia; Sadam Ahmed Elayah; Lin-yang Xie; Hao Cui; Jun-bo Tu; Si-jia Na (Inflammation Research, 2024)

Porphyromonas gingivalis promotes the progression of oral squamous cell carcinoma by stimulating the release of neutrophil extracellular traps in the tumor immune microenvironment - Zhi-chen Guo; Si-li Jing; Xin-yu Jia; Sadam Ahmed Elayah; Lin-yang Xie; Hao Cui; Jun-bo Tu; Si-jia Na (Inflammation Research, 2024)

Biotransformation activities of fungal strain apiotrichum sp. IB-1 to ibuprofen and naproxen - Liang Peng; Hui Yun; Jing Ji; Wenjie Zhang; Ting Xu; Si Li; Zhenfei Wang; Li Xie; Xiangkai Li (Archives of Microbiology, 2024)

Miocene Equisetum tubers from the Wulan Basin, Northeast Qinghai-Tibetan Plateau and their paleoecological significance - Zhen-Dong Cao; Peng Zhang; Si-Hang Zhang; Yi-Hong Yang; Jia-Yi Chen; Li-Ming Liu; Xiang-Chuan Li; San-Ping Xie (Palaeoworld, 2024)

Individual self-regulation, external monitoring, and farmers’ safe production behavior: Evidence from the Kuan-chung Plain, China - Zhe Chen; Xiaojing Li; Wei Si; Shouhong Xie; Xianli Xia (Journal of Environmental Management, 2024)

Interaction of 17α-ethinylestradiol and methyltestosterone in western mosquitofish (Gambusia affinis) across two generations - Guo-Yong Huang; Gui-Zhen Fang; Wen-Jun Shi; Xiao-Pei Li; Chen-Si Wang; Hong-Xing Chen; Lingtian Xie; Guang-Guo Ying (Aquatic Toxicology, 2024)

Correction: Seismic response characteristics and performance improvement of near-fault continuous rigid-frame bridges - Jun Li; Long-He Xu; Xing-Si Xie (Bulletin of Earthquake Engineering, 2024)

Seismic response characteristics and performance improvement of near-fault continuous rigid-frame bridges - Jun Li; Long-He Xu; Xing-Si Xie (Bulletin of Earthquake Engineering, 2024)

Hydrate formation significantly decreases the uplifting rate of methane bubble from the seafloor to the upper water column - Jingchun Feng; Yan Xie; Li Tang; Pian Li; Zhenwu Zhou; Si Zhang; Zhifeng Yang; Yi Wang (Science Bulletin, 2023)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

Fundicoccus culcitae sp. nov., a novel potential bacteriocin producing bacterium isolated from a spoiled eye mask - Gang Zhou; Lei Gao; Bao-Zhu Fang; Ying-Si Wang; Hong-Bing Tao; Xia Wen; Qian Wang; Xiao-Mo Huang; Qing-Shan Shi; Wen-Jun Li; Xiao-Bao Xie (Antonie van Leeuwenhoek, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Kinetics study on the catalytic recombination of non-premixed hydrogen–oxygen system: Effects of initial temperature, oxygen flow rate, and hydrogen diffusion time - Xuan Li; Si-Yuan Zhou; Jing Zhang; Zhuo-Wei Guo; Man-Qi Guan; Bin Li; Dan Zhang; Yong-Xu Wang; Li-Feng Xie (Fuel, 2023)

Low-resistance local components design method based on topology optimization: A case study of a duct tee - Yan Tian; Ran Gao; Mengchao Liu; Angui Li; Xin Dong; Shengrui Yu; Xiaojie Xie; Tong Li; Pengfei Si (Building and Environment, 2023)

Comprehensive analysis of circular RNAs in nasopharyngeal cancer - Si-Yu Zhu; Xiao-Yi Wang; Hui Xie; Li-Zhi Liu (Genes & Genomics, 2023)

Description of a natural infection with decapod iridescent virus 1 in farmed swimming crab - Liang Qiu; Xiao-Meng Guo; Guo-Si Xie; Yong-Hui Feng; Jing-Yi Xing; Chen Li; Bing Yang; Jie Huang (Aquaculture, 2023)

Diverse diterpenoids from Callicarpa rubella Lindl. as natural inhibitors of macrophage foam cell formation - Xue-Wen Wu; Qian-Lang Feng; Yi-Fan Xie; Si-Chen Song; Bin Cheng; Yan Ma; Qing Li; Xu Ji; Xiao-Li Li; Guang Cao; Wei-Lie Xiao (Phytochemistry, 2023)

Systematic analyzing a five- miRNA panel and its diagnostic value of plasma expression in colorectal cancer - Si-Qi Li; Li-Ye Xie; Zheng-Min Cai; Hao-Tang Wei; Ming-Zhi Xie; Bang-Li Hu; Shu-Fang Ning (Molecular Biology Reports, 2023)

Coupling of the Calculated Freezing and Thawing Front Parameterization in the Earth System Model CAS-ESM - Ruichao Li; Jinbo Xie; Zhenghui Xie; Binghao Jia; Junqiang Gao; Peihua Qin; Longhuan Wang; Si Chen (Advances in Atmospheric Sciences, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

GL-Net: Semantic segmentation for point clouds of shield tunnel via global feature learning and local feature discriminative aggregation - Jincheng Li; Zhenxin Zhang; Haili Sun; Si Xie; Jianjun Zou; Changqi Ji; Yue Lu; Xiaoxu Ren; Liuzhao Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Peracetic acid activation via the synergic effect of Co and Fe in CoFe-LDH for efficient degradation of pharmaceuticals in hospital wastewater - Zhi-Hui Xie; Chuan-Shu He; Yong-Li He; Shu-Run Yang; Si-Ying Yu; Zhaokun Xiong; Ye Du; Yang Liu; Zhi-Cheng Pan; Gang Yao; Bo Lai (Water Research, 2023)

Exposure to estrone disrupts the endocrine system of western mosquitofish (Gambusia affinis) - Dong-Qiao Lei; Guo-Yong Huang; Shu-Qing Qiu; Xiao-Pei Li; Chen-Si Wang; Gui-Zhen Fang; Lingtian Xie; Guang-Guo Ying (Aquatic Toxicology, 2023)

Catalytic pyrolysis of 5-Amino-1H-Tetrazole with copper and its oxide: A deep insight into the combustion mechanism for high nitrogen compound - Si-Yuan Zhou; Jiu Chen; Xuan Li; Fan Jia; Dan Zhang; Li-Feng Xie; Bin Li; Lin Jiang (Fuel, 2023)

Effect of multi-type oxides on the catalytic pyrolysis behaviors of 5-amino-1H-tetrazole - Jiu Chen; Quan Liu; Xian-Zhao Song; Si-Yuan Zhou; Bin Li; Li-Feng Xie; Guang-Cheng Yang; Cheng-Yan Cao; Song Lu; Dan Zhang (Fuel, 2023)

Experimental investigation on the temperature characteristics and hydrogen elimination effect of non-premixed hydrogen-oxygen recombination reaction at ambient temperature - Xuan Li; Jing Zhang; Si-Yuan Zhou; Bin Li; Dan Zhang; Li-Feng Xie (Fuel, 2023)

Controlling sp3 defect density of carbon-based catalysts by defining a limiting space - Qianjie Xie; Wenfang Si; Zheng Wang; Yu Shu; Cong Li; Yehua Shen; Hiroshi Uyama (Chemical Engineering Journal, 2023)

Outer membrane protein of OmpF contributes to swimming motility, biofilm formation, osmotic response as well as the transcription of maltose metabolic genes in Citrobacter werkmanii - Gang Zhou; Ying-Si Wang; Hong Peng; Hui-Zhong Liu; Jin Feng; Su-Juan Li; Ting-Li Sun; Cai-Ling Li; Qing-Shan Shi; Xiao-bao Xie (World Journal of Microbiology and Biotechnology, 2023)

Contextual Fear Learning and Extinction in the Primary Visual Cortex of Mice - Xiaoke Xie; Shangyue Gong; Ning Sun; Jiazhu Zhu; Xiaobin Xu; Yongxian Xu; Xiaojing Li; Zhenhong Du; Xuanting Liu; Jianmin Zhang; Wei Gong; Ke Si (Neuroscience Bulletin, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Response of the metabolic and autophagy pathways in Mytilus under starvation - Bing Xie; Chuan-yue Chen; Xiaolin Zhang; Si-yuan Li; Zhong-qi Gu; Ji Huang; Jian-yu He; Peng-zhi Qi; Bao-ying Guo; Zhi Liao; Xiaojun Yan (Frontiers in Marine Science, 2022)
Being an industrially valuable species of bivalve, Mytilus is widespread in the area around the eastern coast of China. Starvation is an environmental stress that mussels often encounter in their growth. However, few report carried out on the physiological and biochemical response and molecular regulation and adaptation mechanism of mussels under starvation. To illustrate the molecular mechanism of hosts of Mytilus to starvation, the gill transcriptome was used for analysis before and after 9 days of starvation in Mytilus using the Illumina/HiSeq-2000 deep sequencing platform, accompanied by the study of differentially expressed genes (DEGs). In total, 42.137 GB of clean data were obtained from six sample libraries, the average amount of clean data of each sample is 7.023 GB, and 58,540 unigenes that average 780 bp in length were assembled. Unigenes were illustrated by commenting them against the NR, Swiss-Prot, Pfam, String, GO and KEGG databases. After 9 days of starvation, 2,188 and 2,672 genes were determined to be significantly up- or down-regulated expression genes, separately. Amongst, 4,860 genes were associated with 260 pathways, contains vital enrichment pathways, such as “Metabolic”, “PI3K-Akt signaling pathway”, “Phagosome”, “Apoptosis” and “Lysosome”. In inclusion, autophagy cells were investigated by an electron microscopy, alongside further observations of the expression of autophagy-related genes in gill tissue before and after starvation. The data indicates that the amount of autophagosomes increased and found that atg2 , atg6 and atg13 were significantly up-regulated. These results indicated that Mytilus may use autophagy to cope with their damage after starvation. With our research results, we have contributed to a deeper understanding of the role of the molecular mechanisms of immune defence in Mytilus under environmental stress, which has given insights into mussel breeding and the understanding of the molecular mechanisms of Mytilus immune system.

Damage evolution and fragmentation behavior of pyramid cut blasting under uniaxial compression - Si-yu Chen; Li-yun Yang; Ai-yun Yang; Chen Huang; Huan-zhen Xie (Journal of Mountain Science, 2022)

CAS-LSM Datasets for the CMIP6 Land Surface Snow and Soil Moisture Model Intercomparison Project - Binghao Jia; Longhuan Wang; Yan Wang; Ruichao Li; Xin Luo; Jinbo Xie; Zhenghui Xie; Si Chen; Peihua Qin; Lijuan Li; Kangjun Chen (Advances in Atmospheric Sciences, 2021)
The datasets of the five Land-offline Model Intercomparison Project (LMIP) experiments using the Chinese Academy of Sciences Land Surface Model (CAS-LSM) of CAS Flexible Global-Ocean-Atmosphere-Land System Model Grid-point version 3 (CAS FGOALS-g3) are presented in this study. These experiments were forced by five global meteorological forcing datasets, which contributed to the framework of the Land Surface Snow and Soil Moisture Model Intercomparison Project (LS3MIP) of CMIP6. These datasets have been released on the Earth System Grid Federation node. In this paper, the basic descriptions of the CAS-LSM and the five LMIP experiments are shown. The performance of the soil moisture, snow, and land-atmosphere energy fluxes was preliminarily validated using satellite-based observations. Results show that their mean states, spatial patterns, and seasonal variations can be reproduced well by the five LMIP simulations. It suggests that these datasets can be used to investigate the evolutionary mechanisms of the global water and energy cycles during the past century.

Increases in Anthropogenic Heat Release from Energy Consumption Lead to More Frequent Extreme Heat Events in Urban Cities - Bin Liu; Zhenghui Xie; Peihua Qin; Shuang Liu; Ruichao Li; Longhuan Wang; Yan Wang; Binghao Jia; Si Chen; Jinbo Xie; Chunxiang Shi (Advances in Atmospheric Sciences, 2021)

RNA-Seq revealed that infection with white tip nematodes could downregulate rice photosynthetic genes - Hong-Le Wang; Si-Hua Yang; Mei Lv; Shan-Wen Ding; Jun-Yi Li; Chun-Ling Xu; Hui Xie (Functional & Integrative Genomics, 2020)

Exploring the Potential of Mesoporous Silica as a Carrier for Puerarin: Characterization, Physical Stability, and In Vivo Pharmacokinetics - Zhi Wang; Bei-Ni Ye; Yong-Tai Zhang; Jian-Xu Xie; Wan-Si Li; Hong-Tao Zhang; Ying Liu; Nian-Ping Feng (AAPS PharmSciTech, 2019)

Hysteretic behavior and failure mechanism of an assembled self-centering brace - Long-He Xu; Xing-Si Xie; Shi-Qian Yao; Zhong-Xian Li (Bulletin of Earthquake Engineering, 2019)

Effects of cadmium stress on the antioxidant system and chlorophyll fluorescence characteristics of two Taxodium clones - Ying-Li Ma; Hui-Fang Wang; Ping Wang; Chao-Guang Yu; Si-Qian Luo; Yu-Feng Zhang; Yin-Feng Xie (Plant Cell Reports, 2018)

Occurrence and distribution of antibiotic resistance genes in the sediments of drinking water sources, urban rivers, and coastal areas in Zhuhai, China - Aolin Li; Lujun Chen; Yan Zhang; Yile Tao; Hui Xie; Si Li; Weiling Sun; Jianguo Pan; Zhidong He; Chaoan Mai; Yingying Fan; Huanchao Xian; et al. (Environmental Science and Pollution Research, 2018)

Transcriptome analysis of differentially expressed genes in rabbits’ ovaries by digital gene-expression profiling - Tao Huang; Ya-dong Wang; Ming-ming Xue; Xue Feng; Cai-Xia Sun; An-si Wang; Shu-yu Xie; Meng Zhang; Gui-Rong Sun; Ming Li (Genes & Genomics, 2018)

Anticancer effect of Polyphyllin Ι in colorectal cancer cells through ROS-dependent autophagy and G2/M arrest mechanisms - Si Yu; Lijiao Wang; Zhixing Cao; Daoyin Gong; Qianyi Liang; Hanting Chen; Huizhu Fu; Wenwen Wang; Xue Tang; Zihao Xie; Yang He; Cheng Peng; et al. (Natural Product Research, 2018)

Establishment of an embryonic cell line from the American cockroach Periplaneta americana (Blattaria: Blattidae) and a preliminary study of telomerase activity changes during the culturing process - Xin Zhang; Ying Feng; Wei-Feng Ding; Xian Li; Si-Cong Xie (In Vitro Cellular & Developmental Biology - Animal, 2018)

Molecular Dynamics Simulation Reveals Unique Interplays Between a Tarantula Toxin and Lipid Membranes - Lei Wu; Si-Si Xie; Er Meng; Wen-Ying Li; Long Liu; Dong-Yi Zhang (The Journal of Membrane Biology, 2017)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

Early postnatal stress suppresses the developmental trajectory of hippocampal pyramidal neurons: the role of CRHR1 - Rui Liu; Xiao-Dun Yang; Xue-Mei Liao; Xiao-Meng Xie; Yun-Ai Su; Ji-Tao Li; Xiao-Dong Wang; Tian-Mei Si (Brain Structure and Function, 2016)

Responses of wheat and rice to factorial combinations of ambient and elevated CO 2 and temperature in FACE experiments - Chuang Cai; Xinyou Yin; Shuaiqi He; Wenyu Jiang; Chuanfei Si; Paul C. Struik; Weihong Luo; Gang Li; Yingtian Xie; Yan Xiong; Genxing Pan (Global Change Biology, 2016)
Elevated CO 2 and temperature strongly affect crop production, but understanding of the crop response to combined CO 2 and temperature increases under field conditions is still limited while data are scarce. We grew wheat ( Triticum aestivum L.) and rice ( Oryza sativa L.) under two levels of CO 2 (ambient and enriched up to 500 μmol mol −1 ) and two levels of canopy temperature (ambient and increased by 1.5–2.0 °C) in free‐air CO 2 enrichment (FACE) systems and carried out a detailed growth and yield component analysis during two growing seasons for both crops. An increase in CO 2 resulted in higher grain yield, whereas an increase in temperature reduced grain yield, in both crops. An increase in CO 2 was unable to compensate for the negative impact of an increase in temperature on biomass and yield of wheat and rice. Yields of wheat and rice were decreased by 10–12% and 17–35%, respectively, under the combination of elevated CO 2 and temperature. The number of filled grains per unit area was the most important yield component accounting for the effects of elevated CO 2 and temperature in wheat and rice. Our data showed complex treatment effects on the interplay between preheading duration, nitrogen uptake, tillering, leaf area index, and radiation‐use efficiency, and thus on yield components and yield. Nitrogen uptake before heading was crucial in minimizing yield loss due to climate change in both crops. For rice, however, a breeding strategy to increase grain number per m 2 and % filled grains (or to reduce spikelet sterility) at high temperature is also required to prevent yield reduction under conditions of global change.

A purple acid phosphatase plays a role in nodule formation and nitrogen fixation in Astragalus sinicus - Jianyun Wang; Zaiyong Si; Fang Li; Xiaobo Xiong; Lei Lei; Fuli Xie; Dasong Chen; Yixing Li; Youguo Li (Plant Molecular Biology, 2015)

Secretory expression of a bispecific antibody targeting tumor necrosis factor and ED-B fibronectin in Pichia pastoris and its functional analysis - Meng-yuan Liu; Xue-ping Hu; Mian Xie; Si-jing Jiang; Lu-jun Li; Dong-xu Liu; Xiao-song Yang (Biotechnology Letters, 2014)

Structure-based design, synthesis, and anticonvulsant activity of isatin-1-N-phenylacetamide derivatives - Chao Xie; Li-Ming Tang; Fu-Nan Li; Li-Ping Guan; Cheng-Yan Pan; Si-Hong Wang (Medicinal Chemistry Research, 2014)

A New Piezochromic Fluorescence and Aggregation-Induced Emission Compound Containing Tetraphenylethylene and Triphenylamine Moieties with Morphology-alterable Property - Xie Zhou; Hai-yin Li; Zhen-guo Chi; Bing-jia Xu; Xi-qi Zhang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2012)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)